2019
DOI: 10.1093/brain/awz390
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic HSCT for adult-onset leukoencephalopathy with spheroids and pigmented glia

Abstract: Adult-onset leukoencephalopathy with spheroids and pigmented glia (ALSP) is an autosomal dominant leukoencephalopathy caused by mutations in colony stimulating factor 1 receptor (CSF1R). Here we report clinical and imaging outcomes following allogeneic haematopoietic stem cell transplantation (HSCT) in two patients with ALSP at the University of California, San Francisco between January 2016 and December 2017. Patient 1 proceeded to transplantation at age 53 with a haplo-identical sibling donor. Patient 2, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 24 publications
5
48
0
Order By: Relevance
“…This meaningful finding is further supported by a recent study convincingly showing the effectiveness of HSCT from human leukocyte antigen-matched wild-type CSF1R gene donors in two CSF1R-related leukoencephalopathy patients [95]. These patients did not show any signs of acute or chronic graft-versus-host disease after HSCT, but experienced worsened neurological symptoms such as parkinsonism after transplantation [95]. During the follow-up period one patient developed pneumonia and the other suffered from new localization-related seizures.…”
Section: Microglial Replacement By Hematopoietic Stem Cell Transplantsupporting
confidence: 70%
See 4 more Smart Citations
“…This meaningful finding is further supported by a recent study convincingly showing the effectiveness of HSCT from human leukocyte antigen-matched wild-type CSF1R gene donors in two CSF1R-related leukoencephalopathy patients [95]. These patients did not show any signs of acute or chronic graft-versus-host disease after HSCT, but experienced worsened neurological symptoms such as parkinsonism after transplantation [95]. During the follow-up period one patient developed pneumonia and the other suffered from new localization-related seizures.…”
Section: Microglial Replacement By Hematopoietic Stem Cell Transplantsupporting
confidence: 70%
“…A previous study reported an affected individual who underwent HSCT from her sibling remained stable for more than 15 years [96]. This meaningful finding is further supported by a recent study convincingly showing the effectiveness of HSCT from human leukocyte antigen-matched wild-type CSF1R gene donors in two CSF1R-related leukoencephalopathy patients [95]. These patients did not show any signs of acute or chronic graft-versus-host disease after HSCT, but experienced worsened neurological symptoms such as parkinsonism after transplantation [95].…”
Section: Microglial Replacement By Hematopoietic Stem Cell Transplantsupporting
confidence: 62%
See 3 more Smart Citations